Impacts of Nitrogen and Phosphorus Fertilization on Biomass, Polyphenol Contents, and Essential Oil Yield and Composition of Vitex negundo Linn - Li-Chen Peng; Lean-Teik Ng (Agriculture, 2022)
Nutrient management has increasingly become important in producing quality medicinal plant materials. Vitex negundo is an important perennial medicinal plant widely distributed in tropical Asia and Africa. This study aimed to examine the effects of nitrogen (N) and phosphorus (P) fertilization on the biomass, polyphenol contents, and essential oil yield and composition in field cultivated V. negundo. Two field experiments were conducted; one was performed on three different rates of N fertilizer (50, 100, and 200 kg-N ha−1), and the other was on different P fertilizer rates (50, 100, and 200 kg-P ha−1), with their respective control groups receiving no fertilization under field conditions. The results showed that at 200 kg-P ha−1, V. negundo had the highest biomass and essential oil yield, the highest number of volatile components (45 compounds), and the content of bioactive ingredients (<semantics>β</semantics>-caryophyllene and eremophilene). Polyphenol contents were not significantly different between treatments. This study indicates that 200 kg-P ha−1 (NPK ratio of 1:2:1) treatment positively affects the yield of biomass, essential oils, and bioactive compounds in field cultivated V. negundo.